Meta-stable beta titanium alloy secondary alpha phase morphological characteristic regulation and control method

Through the combined process of solid solution, aging and redissolution treatment, the morphology characteristics of the secondary α phase in the metastable β titanium alloy are controlled, solving the problem of difficulty in fine control in the existing technology and improving the mechanical properties of the alloy.

CN119351919APending Publication Date: 2025-01-24NORTHWESTERN POLYTECHNICAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411593032.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The prior art is difficult to finely regulate the morphological characteristics of the secondary α phase in metastable β-titanium alloys, affecting the mechanical properties of the alloy.

Method used

Through the combined process of solid solution treatment, aging treatment and re-dissolution treatment, the distribution density, size and morphological characteristics of the secondary α phase are controlled to achieve fine control of its morphological characteristics.

Benefits of technology

It effectively changes the distribution density and morphological characteristics of the secondary α phase, achieves fine control of the morphological characteristics of the secondary α phase, and improves the mechanical properties of the metastable β titanium alloy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119351919A_ABST
    Figure CN119351919A_ABST
Patent Text Reader

Abstract

The invention discloses a metastable beta titanium alloy secondary alpha phase morphological characteristic regulation and control method, and relates to the technical field of titanium alloy heat treatment. The method comprises the following steps: carrying out solution treatment on a metastable beta titanium alloy sample, and then carrying out water quenching to room temperature to prepare an intermediate sample I; aging treatment is conducted; and then carrying out water quenching to the room temperature to obtain the high-strength wear-resistant aluminum alloy. According to the method, the distribution density, size and crystallographic variant combination characteristics of the secondary alpha phase in the crystal are effectively changed, so that fine regulation and control of the morphological characteristics (clustered clusters, triangular cone clusters or coarse alpha-phase lath tissues) of the secondary alpha phase are realized. The method solves the problem that in the prior art, a method capable of finely regulating and controlling crystallographic characteristics and combination forms of the secondary alpha phase is lacked.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of titanium alloy heat treatment, and in particular to a method for regulating the morphological characteristics of a secondary α phase of a metastable β titanium alloy. Background Art

[0002] Metastable titanium alloys have low density, good hardenability, and a large space for regulating microstructure and mechanical properties. They are widely used in the aerospace industry and are currently used to manufacture important load-bearing components of Airbus A380 and Boeing 787 passenger aircraft. The mechanical properties of metastable titanium alloys are significantly affected by the second phase. Among all kinds of common precipitated phases, the secondary α phase precipitated by aging is the most important strengthening phase of metastable titanium alloys. Its morphological characteristics, such as changes in distribution density, size, and variant combination, will significantly affect the mechanical properties of metastable β titanium alloys.

[0003] Related studies have shown that fine secondary α phase (small size, high density) can significantly reduce the mean free path of dislocations, thereby improving the strength of the alloy, while coarse α phase is conducive to maintaining the plasticity of the alloy. How to achieve fine control of the morphological characteristics of the α phase (distribution density, size and combination characteristics) is an important technical problem that needs to be solved in the research and development of high-performance titanium alloys.

[0004] At present, the heat treatment method used is usually to obtain a uniformly dispersed and small-sized secondary α phase, and there are few studies that can finely control the crystallographic characteristics and combination morphology of the secondary α phase. In addition, the metastable β titanium alloy structure is sensitive to the heat treatment process. During low-temperature aging, the morphology of the secondary α phase changes in various ways, often gathering into triangular pyramidal clusters and cross-clustered clusters. Its nucleation-growth behavior and crystallographic orientation characteristics are affected by many factors, such as alloy composition, supercooling, aging time, crystal defects, etc., which makes it particularly difficult to achieve fine control of its microscopic morphological characteristics. Therefore, it is urgent to study a method for fine control. Summary of the invention

[0005] In order to solve the above technical problems, the purpose of the present invention is to provide a method for regulating the morphological characteristics of the secondary α phase of a metastable β titanium alloy, so as to solve the problem that there is a lack of methods capable of finely regulating the crystallographic characteristics and combined morphology of the secondary α phase in the prior art.

[0006] The technical solution of the present invention to solve the above technical problem is as follows: a method for controlling the morphological characteristics of the secondary α phase of a metastable β titanium alloy is provided, comprising the following steps:

[0007] (1) The metastable β titanium alloy sample is subjected to solution treatment and then water quenched to room temperature to obtain an intermediate sample 1;

[0008] (2) subjecting the intermediate sample 1 obtained in step (1) to aging treatment to obtain the intermediate sample 2;

[0009] (3) The intermediate sample 2 obtained in step (2) is subjected to a dissolution treatment and then quenched with water to room temperature to obtain.

[0010] On the basis of the above technical solution, the present invention can also be improved as follows:

[0011] Furthermore, in step (1), the metastable β titanium alloy sample is a Ti-12Mo alloy or a Ti-5Al-5Mo-5V-3Cr alloy.

[0012] Furthermore, the mass fraction of Ti in the Ti-12Mo alloy is 88%, and the mass fraction of Mo is 12%; the mass fraction of Ti in the Ti-5Al-5Mo-5V-3Cr alloy is 82%, the mass fraction of Al is 5%, the mass fraction of Mo is 5%, the mass fraction of V is 5%, and the mass fraction of Cr is 3%.

[0013] Furthermore, in step (1), the surface oxide layer of the metastable β titanium alloy sample is removed and then solution treatment is performed.

[0014] Furthermore, in step (1), solution treatment is performed under protective atmosphere or vacuum conditions.

[0015] Further, in step (1), at (T β +50)-(T β+ Solution treatment at 150)℃ for 30-60min, where T β is the phase transition temperature of β phase in metastable β titanium alloy.

[0016] Furthermore, in step (1), the intermediate sample 1 obtains a full β-phase equiaxial initial structure.

[0017] Furthermore, in step (2), an aging treatment is performed at 500-700° C. for 5-30 min.

[0018] Furthermore, in step (2), aging treatment is performed at 600° C. for 20 min.

[0019] Furthermore, in step (2), the intermediate sample 2 obtained a high-density secondary α phase distributed inside the β grains and on the grain boundaries.

[0020] Further, in step (3), at (T β -50)-T β Dissolve back at ℃ for 5-20min.

[0021] The beneficial effect of adopting the above further technical solution is: by adopting the dissolution treatment and then water quenching, a secondary α variant with specific organizational characteristics is obtained, that is, a thick secondary α lath is obtained.

[0022] Further, in step (3), at (Tβ The mixture was dissolved at -30℃ for 15min.

[0023] Furthermore, in step (3), the intermediate sample 2 obtained in step (2) is first quenched in water, then subjected to a dissolution treatment, and finally quenched in water to room temperature to obtain.

[0024] The beneficial effect of adopting the above further technical solution is: by adopting two water quenchings before and after the dissolution treatment, a secondary α variant with specific organizational characteristics is obtained, that is, a specific triangular pyramidal cluster is obtained.

[0025] Furthermore, in step (3), a secondary α phase with specific morphological characteristics is obtained.

[0026] The present invention also provides a metastable beta titanium alloy secondary alpha phase obtained by the method.

[0027] The present invention has the following beneficial effects:

[0028] 1. The present invention firstly dissolves the primary α phase in the material through a relatively high pre-solution temperature (higher than the phase transition temperature of the β phase) to obtain a full β phase equiaxed initial structure, so that the metastable titanium alloy can precipitate a relatively fine secondary α phase during the subsequent aging process, and reduce exogenous differences such as pre-strain and stress-induced defects inside the grains; then, by controlling the aging temperature and aging time, a fine secondary α phase with different size and morphological characteristics is obtained, and the influence of the aging temperature and aging time on the size and content of the secondary α phase is clarified; on this basis, the distribution density, size and morphological characteristics of the secondary α phase are regulated through a high-temperature dissolution process, thereby achieving fine regulation of the morphological characteristics of the secondary α phase.

[0029] 2. The present invention effectively changes the distribution density, size, and crystallographic variant combination characteristics of the secondary α phase in the crystal, thereby achieving fine control of the secondary α phase morphological characteristics (clustered clusters, triangular pyramidal clusters, or coarse α phase lath structures). Different from the traditional solution-aging treatment that usually obtains a dispersed and dense secondary α phase, the present invention effectively controls the size, spacing, and combination of α phase variants by changing the combination of aging and dissolution process parameters, thereby obtaining clustered clusters, triangular pyramidal clusters, or coarse α phase lath morphological characteristics, and achieving fine control of the metastable β titanium alloy microstructure. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 EBSD images of the secondary α phase morphology characteristics of the final products of Examples 11, 13 and 16;

[0031] Figure 2 is the BSE diagram of the intermediate sample 2 prepared in Example 1;

[0032] Figure 3is the BSE diagram of the intermediate sample 2 prepared in Example 2;

[0033] Figure 4 is the BSE diagram of the intermediate sample 2 prepared in Example 3;

[0034] Figure 5 is the BSE diagram of the intermediate sample 2 prepared in Example 4;

[0035] Figure 6 is the BSE diagram of the intermediate sample 2 prepared in Example 5;

[0036] Figure 7 is the BSE diagram of the intermediate sample 2 prepared in Example 6;

[0037] Figure 8 is the BSE diagram of the intermediate sample 2 prepared in Example 7;

[0038] Fig. 9 is the BSE diagram of the intermediate sample 2 prepared in Example 8;

[0039] Fig.10 is the BSE diagram of the intermediate sample 2 prepared in Example 9;

[0040] Fig.11 is the BSE diagram of the intermediate sample 2 prepared in Example 10;

[0041] Fig.12 is the BSE diagram of the intermediate sample 2 prepared in Example 11;

[0042] Fig.13 is the BSE diagram of the final product obtained in Example 11;

[0043] Fig.14 This is the BSE diagram of the final product obtained in Example 12;

[0044] Fig.15 This is the BSE diagram of the final product obtained in Example 13;

[0045] Fig.16 is the BSE diagram of the intermediate sample 2 prepared in Example 14;

[0046] Fig.17 This is the BSE diagram of the final product obtained in Example 14;

[0047] Fig.18 This is the BSE diagram of the final product obtained in Example 15;

[0048] Fig.19 This is the BSE diagram of the final product obtained in Example 16;

[0049] Fig. 20is the BSE diagram of the intermediate sample 2 obtained in Example 17;

[0050] Fig.21 This is the BSE diagram of the final product obtained in Example 17;

[0051] Fig. 22 is the BSE diagram of the intermediate sample 2 prepared in Example 18;

[0052] Fig.23 This is the BSE diagram of the final product obtained in Example 18. DETAILED DESCRIPTION

[0053] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples are only used to explain the present invention and are not used to limit the scope of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0054] In the following embodiments, the mass fraction of Ti in the Ti-12Mo alloy is 88%, and the mass fraction of Mo is 12%; the mass fraction of Ti in the Ti-5Al-5Mo-5V-3Cr alloy is 82%, the mass fraction of Al is 5%, the mass fraction of Mo is 5%, the mass fraction of V is 5%, and the mass fraction of Cr is 3%.

[0055] Embodiment 1:

[0056] A method for controlling the morphological characteristics of secondary α phase of a metastable β titanium alloy comprises the following steps:

[0057] (1) The metastable β titanium alloy sample (Ti-12Mo) was polished with sandpaper to remove the surface oxide layer to prevent the oxide layer from interfering with the heat treatment effect during the subsequent heat treatment process. Then, the sample was placed in a vacuum quartz tube and heated at 900 °C (T β The sample was solution treated at 821℃ for 30min and then quenched in water to room temperature to obtain the intermediate sample 1 (full β phase equiaxed initial structure).

[0058] (2) The intermediate sample 1 obtained in step (1) was aged at 600° C. (α / β dual phase region) for 30 min to obtain the intermediate sample 2 (high density secondary α phase distributed inside β grains and on grain boundaries).

[0059] Embodiment 2:

[0060] A method for controlling the morphological characteristics of secondary α phase of a metastable β titanium alloy comprises the following steps:

[0061] In step (2), aging treatment is performed at 650° C., and the rest is the same as in Example 1.

[0062] Embodiment 3:

[0063] A method for controlling the morphological characteristics of secondary α phase of a metastable β titanium alloy comprises the following steps:

[0064] (1) The metastable β titanium alloy sample (Ti-5Al-5Mo-5V-3Cr) was polished with sandpaper to remove the surface oxide layer to prevent the oxide layer from interfering with the heat treatment effect during the subsequent heat treatment process. Then, the sample was placed in a vacuum quartz tube and heated at 880°C (T β The sample was solution treated at 830℃ for 30min and then quenched in water to room temperature to obtain the intermediate sample 1 (full β phase equiaxed initial structure).

[0065] (2) The intermediate sample 1 obtained in step (1) was aged at 550° C. (α / β dual phase region) for 20 min to obtain the intermediate sample 2 (high density secondary α phase distributed inside β grains and on grain boundaries).

[0066] Embodiment 4-6:

[0067] A method for controlling the morphological characteristics of secondary α phase of a metastable β titanium alloy comprises the following steps:

[0068] In step (2), aging treatment is performed at 600° C., 650° C., and 700° C., respectively, and the rest is the same as in Example 3.

[0069] Embodiment 7-10:

[0070] A method for controlling the morphological characteristics of secondary α phase of a metastable β titanium alloy comprises the following steps:

[0071] In step (2), the aging treatment is performed at 600° C. for 5 min, 15 min, 25 min, and 30 min, respectively, and the rest is the same as in Example 3.

[0072] Embodiment 11:

[0073] A method for controlling the morphological characteristics of secondary α phase of a metastable β titanium alloy comprises the following steps:

[0074] (1) The metastable β titanium alloy sample (Ti-5Al-5Mo-5V-3Cr) was polished with sandpaper to remove the surface oxide layer to prevent the oxide layer from interfering with the heat treatment effect during the subsequent heat treatment process. Then, it was placed in a protective atmosphere and heated at 880°C (T β The sample was solution treated at 830℃ for 30min and then quenched in water to room temperature to obtain the intermediate sample 1 (full β phase equiaxed initial structure).

[0075] (2) subjecting the intermediate sample 1 obtained in step (1) to aging treatment at 650° C. (α / β dual phase region) for 20 min to obtain the intermediate sample 2 (high density secondary α phase distributed inside β grains and on grain boundaries);

[0076] (3) The intermediate sample 2 obtained in step (2) is dissolved back at 800° C. (near the β transition point) for 10 min, and then quenched with water to room temperature to obtain a secondary α phase with specific morphological characteristics (size, spacing and variant combination).

[0077] Embodiment 12-13:

[0078] A method for controlling the morphological characteristics of secondary α phase of a metastable β titanium alloy comprises the following steps:

[0079] In step (3), the dissolution treatment was performed for 15 min and 20 min respectively, and the rest was the same as in Example 11.

[0080] Embodiment 14-16:

[0081] A method for controlling the morphological characteristics of secondary α phase of a metastable β titanium alloy comprises the following steps:

[0082] In step (2), aging treatment is performed at 700° C. (α / β dual phase region);

[0083] In step (3), the intermediate sample 2 obtained in step (2) is quenched to retain the triangular pyramidal clusters formed during the aging process, and then dissolved back at 800°C (near the β transition point) for 10 min, 15 min, and 20 min, respectively, and finally quenched with water to room temperature to obtain the obtained product. The rest is the same as Example 11.

[0084] Embodiment 17:

[0085] A method for controlling the morphological characteristics of secondary α phase of a metastable β titanium alloy comprises the following steps:

[0086] (1) The metastable β titanium alloy sample (Ti-12Mo) was polished with sandpaper to remove the surface oxide layer to prevent the oxide layer from interfering with the heat treatment effect during the subsequent heat treatment process. Then, the sample was placed in a vacuum quartz tube and heated at 921°C (T β The sample was solution treated at 821℃ for 40min and then quenched in water to room temperature to obtain the intermediate sample 1 (full β phase equiaxed initial structure).

[0087] (2) subjecting the intermediate sample 1 obtained in step (1) to aging treatment at 500° C. (α / β dual phase region) for 30 min to obtain the intermediate sample 2;

[0088] (3) The intermediate sample 2 obtained in step (2) is dissolved back at 771° C. (near the β transition point) for 18 min, and then quenched with water to room temperature to obtain a secondary α phase with specific morphological characteristics (size, spacing and variant combination).

[0089] Embodiment 18:

[0090] A method for controlling the morphological characteristics of secondary α phase of a metastable β titanium alloy comprises the following steps:

[0091] (1) The metastable β titanium alloy sample (Ti-5Al-5Mo-5V-3Cr) was polished with sandpaper to remove the surface oxide layer to prevent the oxide layer from interfering with the heat treatment effect during the subsequent heat treatment process. Then, it was placed in a protective atmosphere and heated at 980°C (T β The sample was solution treated at 830℃ for 60min and then quenched in water to room temperature to obtain the intermediate sample 1 (full β phase equiaxed initial structure).

[0092] (2) subjecting the intermediate sample 1 obtained in step (1) to aging treatment at 700° C. (α / β dual phase region) for 5 min to obtain the intermediate sample 2 (high density secondary α phase distributed inside β grains and on grain boundaries);

[0093] (3) The intermediate sample 2 obtained in step (2) is quenched to retain the triangular pyramidal clusters formed during the aging process, and then dissolved back at 830°C (near the β transition point) for 5 min, and finally quenched with water to room temperature to obtain a secondary α phase with specific morphological characteristics (size, spacing and variant combination).

[0094] Test example

[0095] 1. The final products obtained in Examples 11, 13 and 16 were surface ground, mechanically polished, and microstructured. Figure 1 ( Figure 1 From left to right in the figure are Examples 11, 13 and 16).

[0096] Depend on Figure 1 It can be seen that different morphologies can be obtained by the control method of the present invention, namely, cluster-like clusters, triangular pyramid-like clusters, and thick lath-like morphologies.

[0097] Second, the intermediate sample 2 prepared in Example 1-2 was quenched to retain the microstructure under different aging conditions, and then the surface of the sample was grinded, mechanically polished, and the microstructure was observed. The results are shown in FIG. Figure 2-Figure 3 .

[0098] Depend on Figure 2-Figure 3It can be seen that when aging treatment is carried out in the α / β dual-phase region, as the aging temperature increases, the secondary α phase changes from densely crossed clusters to triangular pyramid clusters, and the density decreases.

[0099] 3. The intermediate sample 2 prepared in Example 3-6 was quenched to retain the microstructure under different aging conditions. The sample surface was then ground and mechanically polished, and the microstructure was observed. The results are shown in FIG. Figure 4-Figure 7 .

[0100] Depend on Figure 4-Figure 7 It can be seen that during the aging treatment in the α / β dual phase region, the size of the secondary α phase decreases with the increase of aging temperature due to the increased difficulty of uniform nucleation. At the same time, the volume fraction of the secondary α phase in the alloy also gradually decreases.

[0101] 4. The intermediate sample 2 obtained in Example 7-10 was quenched to retain the microstructure under different aging conditions. The surface of the sample was then ground and mechanically polished, and the microstructure was observed. The results are shown in Figure 8-Figure 11 .

[0102] Depend on Figure 8-Figure 11 It can be seen that during the aging treatment in the α / β dual-phase region, with the extension of aging time, the secondary α phase triangular pyramidal clusters in the grain gradually coarsen and evolve into clustered clusters evenly distributed in the grain, while the secondary α phase at the grain boundary grows along the grain boundary into the grain, gradually forming a coarse grain boundary Widmanstätten structure.

[0103] 5. The surfaces of the intermediate sample 2 obtained in Example 11 and the final products obtained in Examples 11-13 were respectively ground, mechanically polished, and microstructured. The results are shown in Figure 12-Figure 15 (in, Fig.13 and Figure 1 The leftmost picture in the figure shows different parts of the same product. Fig.15 and Figure 1 The middle picture shows a different part of the same product).

[0104] Depend on Fig.12 It can be seen that after aging treatment in the dual-phase region, the secondary α phase has a large density and a small size, and is densely distributed in the grain in the form of triangular pyramid clusters or distributed at the grain boundary in the form of Widmanstätten structure. Fig.12 and Figure 13-Figure 15, the morphology and density characteristics of the secondary α phase have changed. On the one hand, the dissolution treatment causes the triangular pyramidal clusters of the secondary α phase distributed in the crystal to disappear, leaving only the coarse secondary α variants distributed in the crystal and the clustered clusters near the grain boundary (gradually evolving into the grain boundary Widmanstätten structure as the dissolution time increases). On the other hand, in addition to the morphological changes, the dissolution treatment also significantly changes the size and volume fraction of the secondary α phase. As the dissolution and heat preservation treatment time increases, the size of the secondary α phase gradually decreases, the length of the secondary α phase structure near the grain boundary gradually decreases, and the density of the secondary α phase in the crystal gradually decreases. In short, the clustered morphology of the secondary α phase after this dissolution treatment disappears, and the secondary α phase with different crystallographic orientations is sparsely distributed in the crystal, thereby obtaining a microstructure composed of specific secondary α variant laths.

[0105] 6. The surfaces of the intermediate sample 2 obtained in Example 14 and the final products obtained in Examples 14-16 were respectively ground, mechanically polished, and microstructured. The results are shown in Figure 16-Figure 19 (in, Fig.19 and Figure 1 The rightmost picture in the figure shows different parts of the same product).

[0106] Depend on Fig.16 It can be seen that after aging treatment in the two-phase region, the secondary α phase spontaneously forms V-shaped or triangular pyramidal clusters, which are densely distributed in the β phase matrix. Figure 17-Figure 19 It can be seen that the secondary α phase is mainly sparsely distributed in the crystal in the form of triangular pyramid clusters. At the same time, with the extension of the dissolution time, the secondary α phase almost disappears. In short, through this dissolution scheme, the density of the secondary α phase is effectively reduced without changing the triangular pyramid morphology, and an alloy structure composed of a specific combination of pyramid variants is obtained.

[0107] 7. The surfaces of the intermediate sample 2 and the final product obtained in Example 17 were respectively ground, mechanically polished, and microstructured. The results are shown in Figure 20-21 .

[0108] Depend on Figure 20-21 It can be seen that after high-temperature dissolution treatment, the fine and dense clusters in the crystal almost disappear, and instead evolve into coarse and dense secondary α phases near the grain boundaries.

[0109] 8. The surfaces of the intermediate sample 2 and the final product obtained in Example 18 were respectively ground, mechanically polished, and microstructured. The results are shown in Figure 22-Figure 23 .

[0110] Depend on Figure 22-Figure 23It can be seen that after short-term aging in the two-phase region, the secondary α phase is distributed throughout the crystal in the form of dense triangular pyramids. After the dissolution treatment, the secondary α phase in the crystal is transformed into the matrix, and a specific type of relatively coarse secondary α phase lath is formed at the grain boundary.

[0111] The results of the above examples further verify the feasibility of regulating the multi-level structure of the secondary α phase in the metastable β titanium alloy based on the aging-dissolution treatment scheme.

[0112] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for controlling the morphological characteristics of secondary α phase of metastable β titanium alloy, characterized in that: The following steps are involved: (1) The metastable β titanium alloy sample is subjected to solution treatment and then water quenched to room temperature to obtain an intermediate sample 1; (2) subjecting the intermediate sample 1 obtained in step (1) to aging treatment to obtain the intermediate sample 2; (3) The intermediate sample 2 obtained in step (2) is subjected to a dissolution treatment and then quenched with water to room temperature to obtain.

2. The method for controlling the morphological characteristics of the secondary α phase of a metastable β titanium alloy according to claim 1, characterized in that: In step (1), the metastable β titanium alloy sample is a Ti-12Mo alloy or a Ti-5Al-5Mo-5V-3Cr alloy.

3. The method for controlling the morphological characteristics of the secondary α phase of a metastable β titanium alloy according to claim 1, characterized in that: In step (1), the surface oxide layer of the metastable β titanium alloy sample is removed and then solution treatment is performed.

4. The method for controlling the morphological characteristics of the secondary α phase of a metastable β titanium alloy according to claim 1, characterized in that: In step (1), solution treatment is performed in a protective atmosphere or under vacuum conditions.

5. The method for controlling the morphological characteristics of the secondary α phase of a metastable β titanium alloy according to claim 1, characterized in that: In step (1), at (T β +50)-(T β +150)℃ solution treatment for 30-60min, where T β is the phase transition temperature of β phase in metastable β titanium alloy.

6. The method for controlling the morphological characteristics of the secondary α phase of a metastable β titanium alloy according to claim 1, characterized in that: In step (2), the aging treatment is performed at 500-700° C. for 5-30 min.

7. The method for controlling the morphological characteristics of the secondary α phase of a metastable β titanium alloy according to claim 1, characterized in that: In step (3), at (T β -50)-T β ℃, and then the solution was treated for 5-20 min, wherein T β is the phase transition temperature of β phase in metastable β titanium alloy.

8. The method for controlling the morphological characteristics of the secondary α phase of a metastable β titanium alloy according to claim 1, characterized in that: In step (3), at (T β -30)℃ for 15min, where T β is the phase transition temperature of β phase in metastable β titanium alloy.

9. The method for controlling the morphological characteristics of the secondary α phase of a metastable β titanium alloy according to claim 1, characterized in that: In step (3), the intermediate sample 2 obtained in step (2) is first quenched in water, then subjected to a dissolution treatment, and finally quenched in water to room temperature to obtain the intermediate sample 2.

10. A metastable β titanium alloy secondary α phase, characterized in that: The secondary α phase morphology characteristics of the metastable β titanium alloy are controlled by the method described in any one of claims 1 to 9.